A descriptive profile of age‐specific knee extension flexion strength in elite junior tennis players - Ellenbecker, Todd S (BMJ Group, 2007)
BACKGROUND: Tennis requires repetitive multidirectional movement patterns that can lead to lower extremity injury. Knowledge of population and age‐specific strength parameters can be used during performance enhancement training and rehabilitation of tennis players. OBJECTIVES: The purpose of this study was to generate population and age‐specific descriptive profiles of concentric isokinetic knee extension and flexion strength in elite junior tennis players, and determine whether bilateral differences exist between extremities and across age ranges. METHODS: A total of 103 elite male tennis players (mean (SD) 15.92 (2.14), range 11–21) and 53 female tennis players (mean (SD) 15.0 (2.30, range 11–21) were isokinetically tested on a Cybex 6000 isokinetic dynamometer at 180 and 300°/s to assess bilateral concentric knee extension and flexion strength using a standard bilateral testing protocol. RESULTS: No significant bilateral difference between the dominant (racquet side) lower extremity and the contralateral non‐dominant side were measured in lower extremity knee extension or flexion strength normalised to body weight, or in the hamstring quadriceps strength ratios in male and female subjects. Male subjects did show significant (p<0.001) increases in knee extension and flexion strength across the age ranges from 11–15 years of age to 16–21 years. Female subjects did not show any significant change in the normalised knee extension or flexion strength across age ranges. Hamstring/quadriceps strength ratios were bilaterally symmetric and remained clinically and statistically constant across age ranges for the male and female elite tennis players. CONCLUSIONS: Population and age‐specific isokinetic descriptive data from elite tennis players can provide guidance in the development and monitoring of performance enhancement and rehabilitation programs for elite tennis players. The changes identified in normalised knee extension and flexion strength in elite male tennis players necessitate the use of population and age‐specific descriptive data.